Sistema autônomo de irrigação com Arduino - FLEXA, Vanessa do Socorro Neves (2022)
The interest in irrigation arises from the most varied conditions of climate, soil, culture and socio-economics. There is no ideal irrigation system, capable of meeting all these conditions and the interests involved in an extremely satisfactory manner. In some regions, farmers irrigate manually. Each cut has an irrigation system that is connected to pipes that communicate through records to a system for pumping water from a weir or rivers, most of the time this system chosen to irrigate is the micro sprinkler system. Opening and closing records for each block (a term used by some farmers to name plantations) is manual. This process causes the use of water far beyond what is necessary as it also creates the need for the presence of the farmer to manipulate the records. The automation of a process can involve mechanisms from the simplest to the most complex, this is made possible through the development of mechanical and electro-electronic devices that allow activation without human intervention, for example, the activation and / or deactivation of a process. This work presents the construction of a prototype to automate the process, it is a simple project. The prototype uses sensors for humidity, temperature, rain, solenoid valves and a microcontroller. The system relies on pre- programmed commands to execute the process. Initially the project aims to collaborate with nature and the farmer in order to avoid wasting water and make the process independent of the presence of a person.